2007
DOI: 10.1097/pec.0b013e31815a0653
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Pediatric Trauma Team Management

Abstract: This study demonstrated that an on-site educational intervention was effective in improving the performance of ED teams during simulated pediatric trauma resuscitations. Postintervention performance was more consistent with the Pediatric Advanced Life Support and Advanced Trauma Life Support guidelines. Further studies are needed to determine if improved performance in a simulated scenario leads to improved performance and better clinical outcomes of critically injured children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 28 publications
(14 reference statements)
0
21
0
1
Order By: Relevance
“…Use of simulation-based training shows improvements in learners’ knowledge, skills, attitudes, and performance. 12 15 Moreover, simulation-based training for medical education leads to effective learning as it provides “repetitive practice, ability to integrate into curriculum, ability to alter the degree of difficulty, ability to capture clinical variation, immediate feedback, and approximation of clinical practice.” 16 …”
Section: Introductionmentioning
confidence: 99%
“…Use of simulation-based training shows improvements in learners’ knowledge, skills, attitudes, and performance. 12 15 Moreover, simulation-based training for medical education leads to effective learning as it provides “repetitive practice, ability to integrate into curriculum, ability to alter the degree of difficulty, ability to capture clinical variation, immediate feedback, and approximation of clinical practice.” 16 …”
Section: Introductionmentioning
confidence: 99%
“…Common items found to be deficient included accurately estimating a child's weight, obtaining vascular access, removing the child's clothing, offering parental support, performing an accurate neurological assessment and stabilizing the patient's cervical spine. A follow up study by Dr. Hunt [20] using similar simulation and assessment methods, found that scenario participation with a brief educational intervention was effective in improving performance in follow up testing. Significant overall trauma team performance improvement was shown in a study comparing scenarios conducted in the first 4 months of the study year versus scenarios conducted during the last 4 months of the year following team-based pediatric simulation training at Cincinnati Children's Hospital [21].…”
Section: Discussionmentioning
confidence: 99%
“…A 6-month follow-up trauma scenario was performed to look at the retention of skills and knowledge. This study demonstrated markedly improved performance by pediatric emergency care providers ( 21 ). Other studies have organized trauma simulation training for multidisciplinary pediatric trauma teams and found significant improvement in overall performance after the simulation training ( 22 , 23 ).…”
Section: Resuscitation and Trauma Trainingmentioning
confidence: 80%